Aerobic and anaerobic power characteristics of Saudi elite soccer players - Al-Hazzaa, H. M.; Almuzaini, K. S.; Al-Refaee, S. A.; Sulaiman, M. A.; Dafterdar, M. Y.; Al-Ghamedi, A.; Al-Khuraiji, K. N. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: To assess the aerobic and anaerobic characteristics of Saudi elite soccer players, and to examine the interrelationship between measures of aerobic and anaerobic power in the elite soccer players. METHODS: Participant: twenty-three outfield elite soccer players representing the Saudi national team participated. Their means (+/-SD) for age, body mass, height and estimated fat % were: 25.2+/-2.3 years; 73.1+/-6.8 kg; 177.2+/-5.9 cm; and 12.3+/-2.7%, respectively. Measures: cardiorespiratory parameters, including maximal oxygen uptake (V O2 max), were assessed by open-circuit spirometry during graded treadmill running. Anaerobic power measures were obtained using Wingate anaerobic test, and included peak power (PP), and average power for 5 sec (AP 5), 10 sec (AP 10), 20 sec (AP 20) and 30 sec (AP 30). RESULTS: Mean (+/-SD) values for V O2max in absolute and relative to body mass were 4.16+/-0.34 l.min-1 and 56.8+/-4.8 ml.kg-1.min-1, respectively. Such V O2max value was 118% and 80% of those reported for Saudi college males and distance runners, respectively. The ventilatory anaerobic thereshold (Tvent) averaged 43.6 ml.kg-1.min-1. There were no significant differences in V O2max and Tvent between players based on positions, although the midfielders and the centre-backs had the highest and the lowest individual values for both measures, respectively. Values (+/-SD) of PP and AP 30 were 873.6+/-141.8 W (11.88+/-1.3 W.kg-1), and 587.7+/-55.4 W (8.02+/-0.53 W.kg-1), respectively. Only in absolute PP & AP 30 were the centre-backs significantly superior to the other players. In addition, V O2max was inversely related to PP (r=-0.54; p<0.05) and positively related to AP 30 (r=0.45; p<0.05). CONCLUSIONS: The aerobic power, expressed relative to body mass, of Saudi elite soccer players was in the lower range of values normally reported in the literatures for elite soccer players. Both PP and AP 30 were somewhat lower than values previously reported for elite soccer players from other countries.